2014
DOI: 10.5152/tjbh.2014.2331
|View full text |Cite
|
Sign up to set email alerts
|

Value of Strain Elastography Ultrasound in Differentiation of Breast Masses and Histopathologic Correlation

Abstract: Objective: US elastography is an emerging technique that can be used during breast US examination. The increasing awareness of breast cancer led to an increase in mammography and breast US examinations. The specificity of these techniques is not high enough to prevent unnecessary biopsies. There is still a need for a more specific technique that can overcome this problem. This study aimed to evaluate the value of strain elastography in breast lesions. Materials and Methods:In this study, 110 lesions of 96 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
1
11
1
1
Order By: Relevance
“…The above findings are almost similar to the current study. In another study by [3] done on 96 patients, where the mean age of their patients was 50 years with ranged varied from 19 to 87 years, which is higher with the present study.…”
Section: Methodscontrasting
confidence: 71%
See 1 more Smart Citation
“…The above findings are almost similar to the current study. In another study by [3] done on 96 patients, where the mean age of their patients was 50 years with ranged varied from 19 to 87 years, which is higher with the present study.…”
Section: Methodscontrasting
confidence: 71%
“…As suggested by the American Cancer Society, breast self-examination and clinical breast examination (palpation) are the most frequently used diagnostic tools for detecting breast abnormalities [2]. Breast screening and diagnostic breast imaging also provide early diagnosis of breast cancer [3]. Mammography, the primary screening modality for breast cancer detection, has a sensitivity of 67.8% and an accuracy of 0.70 as described in Berg et al However, its sensitivity drops from 100% in fatty breasts to about 45% for extremely dense breasts.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the technical factors in acquiring elastography data, histological make up of breast lesions can also influence the ES and SR values. 24 In our study, some of the benign lesions with a significant amount of fibrosis showed high ES > 3 and high strain ratios above our cut-off value 3, thereby leading to false positive results. False negative results on ES were three and SR were four (Table 3).…”
Section: Discussionmentioning
confidence: 52%
“…In addition to the technical factors, histopathological makeup of the breast lesions can also influence the ES and SR values,[ 24 ] contributing to the false-positive or false-negative results on elastography. In our study, there were 27 false-positive lesions on conventional ultrasonography, 5 on strain ratio, and 4 on ES [ Table 4 ].…”
Section: Discussionmentioning
confidence: 99%